Design, analysis and fabrication of beach cleaning machine / Muhammad Ashraf Aiman Hairulnizam - Hairulnizam, Muhammad Ashraf Aiman (2023)
There is various type of beach cleaning machine that has been made. But the difference of this project is its simplest to make and use by the users. Other than that, because of the mini size, it is easier to carry anywhere. Next, the identification of the problems for this project is beach pollution has become a hypercritical issue yet many people are still unaware of and care about it at all. In fact, the beach pollution that keeps rising over the years will give an effect to humans, living things, and the environment. Thus, the objective is to analyze beach pollution that has been increasing over the years and design a mini beach clean machine that can remotely control by the users. The fabrication process used is cutting, bending, drilling, grinding, and many more. The material for this machine is mostly aluminum. This is due to the cheap price, lightweight, durability, and anti corrosion. Lastly, the expected result is this project will give numerous benefits to the living things, the environment, and society near the beaches. In conclusion, this machine is can function effectively without any problems to achieve the objective and solve the problems